Neonatal morbidity among African refugee women in Israel: a case–control study - Amir Hadanny; Ronella Marom; Amit Ovental; Reut Doyev; Laurence Mangel; Jacky Herzlich (BMJ Open)
Objectives Reports on neonatal morbidity (NM) among refugees in developed countries remain inconsistent. We aimed to compare NM among infants of African refugees in Israel to the native population based on a large population sample.Design A case–control study.Setting A tertiary hospital in Israel.Participants Data on hospital-based live births of refugee women and their newborns who were born in 2014 and 2017 were retrieved from medical records. Perinatal and neonatal data were compared between the refugee group and the native residents matched for gestational age and year of birth as well as within the refugee group.Primary outcome Prevalence of NM among African refugees in Israel.Results Newborns delivered by 357 refugee women (mean age 30.2 years) and 357 controls (mean age 32.2 years) were analysed. Both groups were similar for the newborns’ weight and gestational age. There were no significant differences in NM between the groups. A within-refugee comparison conducted between 2014 and 2017 yielded significant differences in birth weight (3051.4 vs 3373.6 gr, p<0.001, 95% CI (198.3 to 446.2), d=0.56), the number of twin deliveries (10 vs 4, p=0.002, Φ=0.173), the number of neonates evaluated as small for gestational age (15 vs 10, p=0.003, Φ=0.167) and the use of human milk (71% vs 93%, p<0.001, Φ=−0.298).Conclusions We conclude that NM among neonates born to refugee mothers was not higher than that of neonates born to native Israeli mothers. We suggest that successful implementation of health policies for refugees has improved their accessibility to mother–child health services.